Semiaphis nolitangere Aizenberg, 1954 and differences between the genera Semiaphis van der Goot, 1913 and Hyadaphis Kirkaldy, 1904 - Heikinheimo, Osmo (Entomologica Fennica, 2001)
The life cycle and distribution of Semiaphis nolitangere Aizenberg are cleared, the alate sexupara and the sexual morphs are described, and the differences between the genera Hyadaphis Kirkaldy, 1904 and Semiaphis van der Goot, 1913 are discussed.